The Impact of Google Sites–Based Interactive Media Integrating Sumbang Duo Baleh on the Development of Politeness in Early Childhood - Yulia, Nova; Warmansyah, Jhoni; Jiwon, Lee (Journal of Early Childhood Education and Teaching (JECET), 2025)
Purpose – This study aims to determine the impact of the impact of google sites–based interactive media integrating sumbang duo baleh on the development of politeness in early childhood. Methods – This research employs an experimental method with a pre-experimental design using a one-group pretest-posttest approach. The population consists of all children at Harapan Ibu IslamiC Kindergarten, totaling 52 children, with a sample of 12 children selected through purposive sampling. Data collection techniques involve observation sheets. Findings – The study results indicate that the average pretest score was 18.25. After four treatments, the scores gradually increased: the first treatment yielded 21.58, the second 25.28, the third 28.83, and the fourth 34.58. The posttest average score reached 40.25. These findings demonstrate that interactive Google Sites media based on Sumbang Duo Baleh positively influences the formation of politeness character in early childhood. Research implications/Limitations – This research contributes to integrating technology and local cultural values into early childhood education. The implementation of interactive media based on local wisdom can be an alternative approach to enhancing children's politeness character. These findings provide insights into the effectiveness of technology in character education. Originality/value – This study offers a novel integration of local cultural wisdom (Sumbang Duo Baleh) with digital interactive media using Google Sites, specifically designed for early childhood character education. Such an approach embedding indigenous values into technology-based learning tools remains largely unexplored in early childhood education research.